Adapting social science to the changing focus of international agricultural research. Proceedings of a Rockefeller Foundation-ILCA social science research fellows workshop (International Livestock Research Institute, 2004)
The papers in this proceedings provide a cross section of science research in international agricultural research centres (IARCs), where the objectives and research foci within the Consultative Group on International Agricultural Research (CGIAR) have changed substantially in the 1990s. The book is divided in five sections. The first explores priority setting and research evaluation of commodity programmes. The second looks at institutional issues. The third explores issues related to commodity policies and food security. The fourth looks at the more incipient role of social science in the newer area of natural resource management and biodiversity. The fifth section explores issues related to technology evaluation, adoption and transfer and the role social science in IARCs helps link with social science Development in the national agricultural research system (NARSs) and support division of labor between IARC and NARS research.